Digital Ecosystems and the Paradox of Inclusive Exclusion: Reconceptualizing Business Development Services for Tanzanian MSMEs in the Platform Era - Bukaza Loth Chachage (Pinisi Journal of Social Science, 2025)
The digitization of Business Development Services (BDS) is championed globally as a solution to scale support for Micro, Small, and Medium Enterprises (MSMEs) in emerging economies. In Tanzania, this vision aligns with national strategies and has spurred a proliferation of mobile-based advisory, fintech, and e-commerce platforms. This conceptual paper identifies and theorizes a critical paradox underpinning this digital transition: the phenomenon of inclusive exclusion. While digital BDS platforms ostensibly promote inclusion by broadening access, they simultaneously engineer new, systemic forms of exclusion rooted in asymmetrical data extraction, opaque algorithmic governance, and entrenched platform power. We argue that the prevailing “digital divide” framework is analytically inadequate, as it focuses narrowly on connectivity rather than on the qualitative and power-laden nature of digital inclusion. Synthesizing digital platform theory, the capabilities approach, and critical data studies, we advance a novel Tripartite Framework of Digital BDS Engagement, centered on the interrelated dimensions of Access, Agency, and Algorithms. Through an analysis of Tanzania’s digital BDS ecosystem, including the government’s M-SME Digital Hub, agri-tech services like WeFarm, and fintech lenders such as Tala, we demonstrate how MSMEs are routinely included as data sources and users but excluded from value capture, fair algorithmic treatment, and meaningful control. In response, we propose a Digital BDS Ecosystem Justice Framework built on three core tensions: Automation versus Advisory, Data Extraction versus Empowerment, and Scalability versus Context-Specificity. The paper concludes that transforming digital BDS from a tool of efficient delivery into a platform for genuine entrepreneurial capability development requires embedded participatory governance, robust data sovereignty principles, and a fundamental reorientation from designing for to designing with Tanzanian MSMEs.